2020
DOI: 10.17707/agricultforest.66.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and Behaviour of Bosnian Households Towards Food Waste

Abstract: In order to determine the amount and value of food waste, a regional survey was carried out, among others, in the Bosnia and Herzegovina (BiH), at the beginning of 2016. A number of 581 respondents participated in on-line survey and their answers were processed using descriptive statistics and dualnon-parametric test. The results of the research were presented according to logical units: socioeconomic characteristics of households; general habits when buying food; attitude toward food products shelf life; atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 7 publications
(8 reference statements)
1
10
0
1
Order By: Relevance
“…Individuals in paid work (fulltime or part-time) have more income and consequently tend to buy more food than students, unemployed, etc. Second, consistent with our hypothesis H1, the results showed that household food waste in Serbia is low, as in most developing countries in the Balkan region (Berjan et al 2019;Bogevska et al 2020;Vaško et al 2020;Yildirim et al 2016) and less than what Djekic et al (2019) determined for Serbia in 2019. FW in Serbia is significantly lower than in developed countries [e.g., from 21% (Gunders 2012) to 30% (Yu and Jaenicke 2020) in the US, 22% in the UK (WRAP 2020), and 21-35% in the EU (Caldeira et al 2019)], taking into account the limitations regarding different methodologies used for FW calculations (Bräutigam et al 2014) and that there are differences between studies and in the reliability of data (Corrado and Sala 2018).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Individuals in paid work (fulltime or part-time) have more income and consequently tend to buy more food than students, unemployed, etc. Second, consistent with our hypothesis H1, the results showed that household food waste in Serbia is low, as in most developing countries in the Balkan region (Berjan et al 2019;Bogevska et al 2020;Vaško et al 2020;Yildirim et al 2016) and less than what Djekic et al (2019) determined for Serbia in 2019. FW in Serbia is significantly lower than in developed countries [e.g., from 21% (Gunders 2012) to 30% (Yu and Jaenicke 2020) in the US, 22% in the UK (WRAP 2020), and 21-35% in the EU (Caldeira et al 2019)], taking into account the limitations regarding different methodologies used for FW calculations (Bräutigam et al 2014) and that there are differences between studies and in the reliability of data (Corrado and Sala 2018).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, it is a common practice in Serbia to store and eat leftovers during the next few days. This habit might probably be driven more by socioeconomic factors than by a pro- (Elmenofi et al 2015), Morocco (Abouabdillah et al 2015), Lebanon (Charbel et al 2016), Tunisia (Sassi et al 2016), Montenegro (Berjan et al 2019), Bosnia and Herzegovina (Vaško et al 2020), and North Macedonia (Bogevska et al 2020). Regarding food labeling knowledge, we observed confusion about the interpretation of food labels.…”
Section: Discussionmentioning
confidence: 77%
“…Indeed, household food waste is around 30% of total food waste [ 5 ]. Having in mind the importance of this issue, previous studies have been focusing on consumers’ behaviour, awareness and attitudes toward food waste as well as the causes of food waste in many countries such as Albania [ 6 ], Morocco [ 7 ], Egypt [ 8 ], Italy and Germany [ 9 , 10 ], Finland [ 11 ], Denmark [ 12 ], Holland [ 13 ], USA [ 14 ], Canada [ 15 , 16 ], UK [ 17 ], Turkey [ 18 ], Tunisia [ 19 ], Algeria [ 20 ], Greece [ 21 ], Serbia [ 22 ], Bosnia and Herzegovina [ 23 ], Montenegro [ 24 ] and North Macedonia [ 25 ]. All these studies used different methodologies to estimate food waste.…”
Section: Introductionmentioning
confidence: 99%
“…There has been no substantial shift in the location of food purchases compared to the pre-pandemic situation. As a result, the COVID-19 pandemic had little effect on where people bought their food ( Vaško et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further, during the pandemic, the percentage of some types of food that are thrown away (e.g. fruits and vegetables) slightly increased compared to 2016 ( Vaško et al, 2020 ), which is probably due to the purchase of larger quantities for fear of shortages or due to complex supply.…”
Section: Resultsmentioning
confidence: 99%